2017
DOI: 10.1097/mlr.0000000000000606
|View full text |Cite
|
Sign up to set email alerts
|

Examining Measures of Income and Poverty in Medicare Administrative Data

Abstract: Disparities by economic status are observed in the health status and health outcomes of Medicare beneficiaries. For health services and health policy researchers, one barrier to addressing these disparities is the ability to use Medicare data to ascertain information about an individual's income level or poverty, because Medicare administrative data contains limited information about individual economic status. Information gleaned from other sources-such as the Medicaid and Supplemental Security Income program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…These differences were particularly pronounced for measures of health status (notably, self‐rated health, functional limitations, and hearing and vision impairments) and were sizeable for socioeconomic indicators (specifically, education and income) that are typically not observable to or used by policy makers for risk adjustment. Although policy makers and researchers routinely use dual enrollment to proxy for low SES and poor health in risk adjustment, our results show that this binary categorization belies substantial heterogeneity in what it means to have Medicaid in different states.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…These differences were particularly pronounced for measures of health status (notably, self‐rated health, functional limitations, and hearing and vision impairments) and were sizeable for socioeconomic indicators (specifically, education and income) that are typically not observable to or used by policy makers for risk adjustment. Although policy makers and researchers routinely use dual enrollment to proxy for low SES and poor health in risk adjustment, our results show that this binary categorization belies substantial heterogeneity in what it means to have Medicaid in different states.…”
Section: Discussionmentioning
confidence: 80%
“…Ideally, risk adjustment would be based on the underlying social and clinical constructs for which dual enrollment is intended to proxy. Although administrative data sources provide a limited picture of these risk factors, research has demonstrated how claims can be used to measure constructs such as frailty, disability status, institutionalization, and via linked Census data, income, education, and social supports . Incorporating these measures of medical and social risk may help to account for some state‐level differences in the characteristics of dual enrollees in ways that current risk‐adjustment methods do not.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations